Native and Polyubiquitinated Forms of Dihydroceramide Desaturase Are Differentially Linked to Human Embryonic Kidney Cell Survival - Alsanafi, Mariam (Mol Cell Biol, 2018)
There is controversy concerning the role of dihydroceramide desaturase (Degs1) in regulating cell survival, with studies showing that it can both promote and protect against apoptosis. We have therefore investigated the molecular basis for these opposing roles of Degs1. Treatment of HEK293T cells with the sphingosine kinase inhibitor SKi [2-(p-hydroxyanilino)-4-(p-chlorophenyl)thiazole] or fenretinide, but not the Degs1 inhibitor GT11 {N-[(1R,2S)-2-hydroxy-1-hydroxymethyl-2-(2-tridecyl-1-cyclopropenyl)ethyl]octan-amide}, induced the polyubiquitination of Degs1 (M(r) = 40 to 140 kDa) via a mechanism involving oxidative stress, p38 mitogen-activated protein kinase (MAPK), and Mdm2 (E3 ligase). The polyubiquitinated forms of Degs1 exhibit “gain of function” and activate prosurvival pathways, p38 MAPK, c-Jun N-terminal kinase (JNK), and X-box protein 1s (XBP-1s). In contrast, another sphingosine kinase inhibitor, ABC294640 [3-(4-chlorophenyl)-adamantane-1-carboxylic acid (pyridin-4-ylmethyl)amide], at concentrations of 25 to 50 μM failed to induce formation of the polyubiquitinated forms of Degs1. In contrast to SKi, ABC294640 (25 μM) promotes apoptosis of HEK293T cells via a Degs1-dependent mechanism that is associated with increased de novo synthesis of ceramide. These findings are the first to demonstrate that the polyubiquitination of Degs1 appears to change its function from proapoptotic to prosurvival. Thus, polyubiquitination of Degs1 might provide an explanation for the reported opposing functions of this enzyme in cell survival/apoptosis.